ANTIBACTERIAL SCREENING OF SARGASSUM SP EXTRACT. OPPOSING VIBRIO PARAHAEMOLYTICUS BACTERIA - Datu, Syeiqido Sora; Angraeni; Fatwasari, Fina; Jarir, Dewi Virgiastuti; Sabilah, Anisa Aulia (MSJ : Majority Science Journal, 2024)
Antibiotics cause resistance to pathogenic bacteria, and the emergence of resistance and bacterial pathogenic infections makes scientists try to find new drugs. One of the efforts is to use marine organisms as a natural antibacterial agent, one of them is Sargassum sp. Sargassum sp contains alginate and iodine which are used in the food, pharmaceutical, cosmetic and textile industries. Apart from that, Sargassum sp. contains active compounds of steroids, alkaloids, phenols and triterpenoids which function as antibacterials, can be used to inhibit the growth of Vibrio sp bacteria which is the cause of firefly disease which is most dangerous for tiger prawns. The purpose of this study was to determine the ability of the extract Sargassum sp. In inhibiting the growth of Vibrio parahaemolyticus bacteria with different levels of solvent start with methanol, ethyl asetat, and n-hexane. The rejuvenation of Vibrio parahaemolyticus and Vibrio harveyimelalai bacteria is carried out in two stages, the first is planting on Triptyc Soy Broth (TSB) medium and the second stage is planting on Triptyc Soy Agar (TSA) medium.  Antibacterial sensitivity test using disc diffusion method. The results of the test showed that 1). sargassum sp which is extracted by metanol solvent inhibits the growth of Vibrio parahemolyticus bacteria. 2). sargassum sp which extract by etil sestat and n - heksan solvent can't inhibit the Vibrio parahemolyticus bacteria.